Home country bias in divestment decisions of multinational corporations in the EU - Laura Resmini; Giuseppe Vittucci (European Regional Science Association (ERSA), 2016)
This paper deals with the performance of multinational enterprises (MNEs) during the recent financial crisis in the EU regions. According to the existing literature both foreign affiliates and local territories may benefit one from each other. There is a huge literature suggesting that FDI is sensitive to transparent and open systems that may ensure a good access to local resources, such as human capital, knowledge and technology, as well as regions with enough capacity to 'absorb' the new technology, know-how and management practices brought into their territories by MNEs may enjoy faster economic growth. This implies that MNEs and regions hosting their foreign plants are interlinked; therefore, the (mis)fortunes of one may condition the performance of the other. The economic crisis that affected and still affects most of European regions both within and across countries has further emphasised the importance of this issue. Do regions hosting foreign production plants show a better resilience to crisis? Do MNEs survive better than indigenous firms during this period? And if yes, which characteristics allowed MNEs to better react to the crisis than other firms? In addressing these questions, we first examine if foreign ownership, and the associated involvement in global value chains, was a factor influencing firms' performance and, if so, through which channels. Then, the identified channels are shown to be also important to explain differences across firms in the response to the crisis. To the best of our knowledge, this is the first article addressing systematically the implications of the recent crisis for firms' performance and drawing from it insights about the EU regions resilience to global shocks. Our analyses rely on a comprehensive firm-level dataset including all firms active in the EU before the economic crisis (2006). Both indigenous and foreign firms are considered and several firm's characteristics, i.e. size and experience, the market focus, and the ownership structure, have been accounted for in order to analyse the probability to survive to the crisis of domestic and foreign firms. Micro-data on firms is derived from the AMADEUS database of firm financial accounts which is provided by the Bureau Van Dijk. This paper offers several contributions to the existing debate on the importance of foreign firms for the performance of local economies. First all, it sheds light on the role of MNEs in EU regions resilience to the crisis. Secondly, it helps in understanding whether multinational firms acted as a stabilizer or a propagator of the crisis across EU regions. Finally, identifying firms - both local and foreign - that may improve regions' resilience to the crisis may help design more effective and better targeted policies for enhancing local development and attract foreign firms that suit better within the local context.
Keywords: F23; O52; R12; 330; foreign divestments; EU regions' resilience; survival analysis